Asenapine in the management of impulsivity and aggressiveness in bipolar disorder and comorbid borderline personality disorder: an open-label uncontrolled study - Aguglia, Andrea (Int Clin Psychopharmacol, 2018)
Borderline personality disorder (BPD) often co-occurres with bipolar disorder (BD). Impulsivity and aggressiveness represent core shared features and their pharmacological management is mainly based on mood stabilizers and antipsychotics, although scarce evidence is available for this context of comorbidity. The aim of the present study was to evaluate the role of Asenapine as an adjunctive drug for reducing aggressiveness and impulsivity in a sample of Italian BD type I outpatients with or without a comorbid BPD. This was an observational 12-week open-label uncontrolled clinical study carried out from April to October 2014 in two psychiatric clinics in Sicily. Each patient was treated with asenapine at two dose options, 5 mg (twice daily) or 10 mg (twice daily), and concomitant ongoing medications were not discontinued. We measured impulsivity using the Barratt Impulsiveness Scale (BIS) and aggressiveness using the Aggressive Questionnaire (AQ). For the analysis of our outcomes, patients were divided into two groups: with or without comorbid BPD. Adjunctive therapy was associated with a significant decrease of BIS and AQ overall scores in the entire bipolar sample. Yet, there was no significant difference in BIS and AQ reductions between subgroups. Using a regression model, we observed that concomitant BPD played a negative role on the Hostility subscale and overall AQ score variations; otherwise, borderline co-diagnosis was related positively to the reduction of physical aggression. According to our post-hoc analysis, global aggressiveness scores are less prone to decrease in patients with a dual diagnosis, whereas physical aggressiveness appears to be more responsive to the add-on therapy in patients with comorbidity.